Roof material detection based on object-based approach using WorldView-2 satellite imagery - Taherzadeh, Ebrahim; Mohd Shafri, Helmi Zulhaidi; Shahi, Kaveh (World Academy of Science, Engineering and Technology, 2014)
One of the most important tasks in urban remote sensing is the detection of impervious surfaces (IS), such as roofs and roads. However, detection of IS in heterogeneous areas still remains one of the most challenging tasks. In this study, detection of concrete roof using an object-based approach was proposed. A new rule-based classification was developed to detect concrete roof tile. This proposed rule-based classification was applied to WorldView-2 image and results showed that the proposed rule has good potential to predict concrete roof material from WorldView-2 images, with 85% accuracy.